2012
DOI: 10.1074/jbc.m112.360214
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Activation and Processing of the Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) by a Complex Electrostatic Interaction between the Regulatory Domain and Cytoplasmic Loop 3

Abstract: Background: NEG2 regulates CFTR gating but the mechanism is unknown. Results: A putative NEG2-CL3 electrostatic attraction, possibly weakened by Arg-764/Arg-766 of the R domain, prohibited CFTR activation. A charge exchange between NEG2 and CL3 caused misprocessing. Conclusion: Electrostatic regulation of CFTR activation and processing may be asymmetric at the CL3-R interface. Significance: The CL3-R interface is optimally designed for multiple regulations of CFTR functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 34 publications
3
14
0
Order By: Relevance
“…Both NMR studies are consistent with the unphosphorylated R‐region blocking NBD dimerization as deduced from the recent high‐resolution CFTR structures . An alternative hypothesis is that the unphosphorylated R‐region interacts directly with the CLs of the TMDs, especially CL3, and these interactions keep the channel in a closed state regardless of NBD dimerization . This hypothesis is supported by the position of the new helix described in the human structure between CLs, potentially interacting with CL 3 and 4 and TM12.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Both NMR studies are consistent with the unphosphorylated R‐region blocking NBD dimerization as deduced from the recent high‐resolution CFTR structures . An alternative hypothesis is that the unphosphorylated R‐region interacts directly with the CLs of the TMDs, especially CL3, and these interactions keep the channel in a closed state regardless of NBD dimerization . This hypothesis is supported by the position of the new helix described in the human structure between CLs, potentially interacting with CL 3 and 4 and TM12.…”
Section: Introductionsupporting
confidence: 80%
“…In both zebrafish and human dephosphorylated structures, most of the R‐region is missing but parts of its densities appear localized in the cytoplasmic gap between the NBDs and the TMDs’ cytoplasmic loops, presumably preventing dimerization of the NBDs. The human structure shows an additional helix, corresponding to residues 825‐843 of the R‐region, which contains NEG2 (amino acids 817‐838), a conserved segment with a negative net charge of −9, involved in the channel regulation by phosphorylation . The phosphorylated structures clearly show the conformational changes of TMDs and NBDs.…”
Section: Introductionmentioning
confidence: 99%
“…Once the R domain is phosphorylated by PKA to release its regulatory extension from NBD1 and its C-terminus from ICL3, the highly conserved ICL1/ICL4-NBD1 and ICL2/ICL3-NBD2 swapping interactions in both inward-and 'outward'-facing TMDs facilitate channel opening by ATP binding-induced NBD1-NBD2 dimerization [9][10][11][12][13][24][25][26][27]. However, the released R domain from ICL3 can bind to the highly conserved ICL1-ICL4 interface for optimal channel opening by promoting the tight tetrahelix bundle-induced inwardto-'outward' reorientation of TMDs and the ATP binding-induced NBD1-NBD2 dimerization [3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…The highly conserved ICL1/ICL4-NBD1 and ICL2/ICL3-NBD2 swapping interactions in both TMD reorientations, as indicated by crystallography studies of bacterial ABC transporters TM287-TM288 and Sav1866 [9,10] and confirmed by crosslinking experiments [11][12][13], may facilitate ATP-dependent gating regulation [3]. On the other hand, three R-ICL3 interactions prevent channel opening by prohibiting ATP binding-induced NBD1-NBD2 dimerization or the PKA-triggered ICL1/ICL4-R interaction [4][5][6][7][8]. They include the H-bond between the -OH group of unphosphorylated S768 of the R domain and the imidazole group of H950 of ICL3 [5], the asymmetric electrostatic interaction between K946 of ICL3 and D835, D836, and E838 of the R domain [6], and the Fe 3+ bridge between H950 and H954 of ICL3 and C832, D836, H775, and phosphorylated S768 of the R domain [4].…”
Section: Introductionmentioning
confidence: 92%
“…In contrast, recent metal-free cryo-EM structure of human CFTR revealed that the R domain is surrounded by NBD1 and NBD2 and ICLs 24 . Furthermore, electrophyiological studies showed that the R domain inhibits channel opening not only by preventing the ATP binding-induced NBD1-NBD2 dimerization 2526 but also by interacting with ICL3 via the H-bond, the Fe 3+ bridge and the salt bridge 1516, 2728 . Upon phosphorylation by PKA, the R domain promote channel opening by releasing from ICL3 and the NBD1-NBD2 interface for binding to the ICL1-ICL4 interface and the N-terminal of CFTR 29, 3033 .…”
Section: Cftr Channelmentioning
confidence: 99%